Phenotypic, Productive, and Reproductive Traits of Domestic Yak (Bos grunniens grunniens) in District Chitral, Pakistan (Journal of Agriculture and Biology, 2025)
The aim of the present study was to determine the morphological characteristics, productive and reproductive performance, and herd composition of domestic yak (Bos grunniens grunniens) in Chitral, Khyber Pakhtunkhwa, Pakistan. Among morphological characteristics, 4 physical characteristics and 17 morphometric measurements were studied. For the assessment of productive performance, the data about daily milk yield, daily milk take-off, and mean lactation period were recorded. The reproductive performance observed were puberty age, postpartum anoestrus interval, calving interval, conception rate, and number of calving per lifetime. Results revealed that almost half of the yak population has a black coat color (Yak bulls, 50.38%; Yak cows, 52.33%). Similarly, the prominent muzzle color of yak bulls (52.25%) and yak cows (53.22%) was also black. Majority (93.85%) of the yak bulls were horned whereas, 65.84% of Yak cows were horned only. Yak bulls have higher values for all morphometric measurements than Yak cows. Daily milk production was 1.76±0.11 kg and daily milk uptake was 0.37 kg. The mean lactation period was 143 days. Mean pubertal age of the Yak cow was 33.35±1.41 months, postpartum anestrus interval 105.16±8.50 days, gestation period 257.00±0.46 days, and maximum 5 calving in lifetime.